2019
DOI: 10.1111/tbed.13296
|View full text |Cite
|
Sign up to set email alerts
|

Myxoma virusjumps species to the Iberian hare

Abstract: The study of myxoma virus (MYXV) infections in the European rabbit (Oryctolagus cuniculus) has produced one of the most accepted host–pathogen evolutionary models. To date, myxomatosis has been limited to the European rabbit with sporadic reports in hares. However, reports of widespread mortalities in the Iberian hare (Lepus granatensis) with myxomatosis‐like clinical signs indicate a potential species jump has occurred. The presence of MYXV DNA was confirmed by PCR in 244 samples received from regional veteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…The rabbits were tested for rabbit haemorrhagic disease virus 2 (RHDV2) and MYXV by real time PCR targeting the M000.5 L/R gene [ 17 , 18 ]. The 2.8 kbp insert was investigated by the system described by Dalton et al [ 15 ] using primers 9A/9B and 9E/9F that flank the insertion, allowing the amplification of a 3.1 or 4.6 kbp region in recombinant MYXV or a 300 bp region (absence of insert, using the oligomers 9E/9F) in MYXV. Amplification reactions were carried out in a Bio-Rad CFX96™ Thermal Cycler (Bio-Rad Laboratories Srl, Redmond, USA), using the One Step RT-PCR kit (Qiagen, Hilden, Germany) for RHDV2, and the HighFidelity PCR Master Mix (Roche Diagnostics GmbH, Mannheim, Germany), for MYXV and recombinant MYXV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rabbits were tested for rabbit haemorrhagic disease virus 2 (RHDV2) and MYXV by real time PCR targeting the M000.5 L/R gene [ 17 , 18 ]. The 2.8 kbp insert was investigated by the system described by Dalton et al [ 15 ] using primers 9A/9B and 9E/9F that flank the insertion, allowing the amplification of a 3.1 or 4.6 kbp region in recombinant MYXV or a 300 bp region (absence of insert, using the oligomers 9E/9F) in MYXV. Amplification reactions were carried out in a Bio-Rad CFX96™ Thermal Cycler (Bio-Rad Laboratories Srl, Redmond, USA), using the One Step RT-PCR kit (Qiagen, Hilden, Germany) for RHDV2, and the HighFidelity PCR Master Mix (Roche Diagnostics GmbH, Mannheim, Germany), for MYXV and recombinant MYXV.…”
Section: Methodsmentioning
confidence: 99%
“…The emergence of myxomatosis in the Iberian hare in mid 2018, was caused by a recombinant myxoma virus (first designated as MYXV-Tol, and subsequently ha-MYXV considering its modified tropism towards hares), harbouring an insertion of about 2.8 kbp [ 13 , 14 , 15 , 16 ]. After this, health surveillance in the Iberian hare within the scope of Project +Coelho (investigating MYXV [ 17 ], RHDV2 [ 18 ] and LeHV-5 [ 19 ]) and in the wild rabbit (investigating MYXV and RHDV2 [ 18 ]) was extended to include screening for ha-MYXV as described by Dalton et al [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following purification, the genome of the MYXV was sequenced using high-throughput sequencing, which led to the identification of the recombinant region (~2.8 kb) derived from an unknown poxvirus in the MYXV genome and thus the recombinant strain, MYXV-Tol [8]. Following this report, other studies [9,10] also identified the MYXV containing the same novel~2.8 kb recombinant region.…”
Section: Resultsmentioning
confidence: 93%
“…Hare populations have declined since the late 1960s which is thought to be in part due to disease [7,51,52]. The recent documentation of an outbreak of myxoma virus in hares caused by a prevalent recombinant MYXV-Tol [8][9][10] highlights another threat to the species. As an important food source for many predator species, such as the endangered Iberian lynx (Lynx pardinus), evaluating circulating pathogen populations and monitoring disease spread as well as spillover of pathogens is crucial for the survival of the hare and other species higher on the trophic cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation